Perceived stigma among patients receiving antiretroviral treatment: A prospective randomised trial comparing an m-DOT strategy with standard-of- care in Kenya - Susan Kaai (SAHARA-J, 2010)
HIV and AIDS remain highly stigmatised. Modified directly observed therapy (m-DOT) supports antiretroviral treatment (ART) adherence but little is known about its association with perceived stigma in resource-constrained settings. In 2003, 234 HIV-infected adults enrolled in a two-arm randomised trial comparing a health centre-based m-DOT strategy with standard self-administration of ART. Data on perceived stigma were collected using Berger's HIV stigma scale prior to starting ART and after 12 months. This was a secondary analysis to examine whether perceived stigma was related to treatment delivery. Perceived stigma scores declined after 12 months of treatment from a mean of 44.9 (sd=7.6) to a mean of 41.4 (sd=7.7), (t=6.14, P<0.001). No differences were found between the mean scores of participants in both study arms. Also, no difference in scores was detected using GLM, controlling for socio-demographic characteristics and baseline scores. Findings indicate that a well managed clinic-based m-DOT does not increase perceived HIV-related stigma.